Vanamahotsava: Fodder Tree Species for Himachal Pradesh - Shabnam, Sant Ram (Indian Forester, 1959)
The live-stock population of Himachal Pradesh is described in relation to soil erosion. In order to reduce the pressure of grazing on pasture lands, importance of a vigorous fodder tree planting programme is emphasized. Peculiar topographical, geological and climatic conditions prevailing in the Pradesh and their influence on plant growth are briefly dealt with; and choice of fodder tree species for planting in different climatic zones is indicated.